The Potency and Utilization of Cassava and Sweet Potato Leaves as Feed Resources for Small Ruminant - Juniar Sirait; K Simanihuruk (Indonesian Center for Animal Research and Development, 2010)
Cassava and sweet potato leaves are agricultural byproducts which are potential to be utilized as feed for small ruminants. In year 2009, it is assumed that dry matter productions of cassava and sweet potato leaves are 2,590,929 and 348,008 tons, respectively. Cassava and sweet potato leaves, both contain high level of protein (> 20%) so that they are good protein sources for goats. Cassava leaves, however, contain cyanide acid (HCN) that varied depended on the age and require wilting process before fed to goat. Several experiments on utilization of cassava or sweet potato leaves for small ruminants showed positive responses on animal performance and could replace 50% of concentrate feed. Besides, cassava leaves can reduce worm eggs while sweet potato leaves contain high lutein. At present, the development of cassava and sweet potato is expected to provide feed as byproduct for ruminant. Key words: Cassava, sweet potato, feed resource, ruminant